Diabetes in all hospitalized cases in Germany 2015–2019 and impact of the first COVID-19 year 2020 - Auzanneau, Marie; Eckert, Alexander J.; Fritsche, Andreas; Heni, Martin; Icks, Andrea; Mueller-Stierlin, Annabel S.; Dugic, Ana; Risse, Alexander; Lanzinger, Stefanie; Holl, Reinhard W. (Endocrine Connections, 2023)
Objective: To analyze the proportion of diabetes among all hospitalized cases in Germany between 2015 and 2020. Methods: Using the nationwide Diagnosis-Related-Groups statistics, we identified among all inpatient cases aged ≥ 20 years all types of diabetes in the main or secondary diagnoses based on ICD-10 codes, as well all COVID-19 diagnoses for 2020. Results: From 2015 to 2019, the proportion of cases with diabetes among all hospitalizations increased from 18.3% (3.01 of 16.45 million) to 18.5% (3.07 of 16.64 million). Although the total number of hospitalizations decreased in 2020, the proportion of cases with diabetes increased to 18.8% (2.73 of 14.50 million). The proportion of COVID-19 diagnosis was higher in cases with diabetes than in those without in all sex and age subgroups. The relative risk (RR) for a COVID-19 diagnosis in cases with vs without diabetes was highest in age group 40–49 years (RR in females: 1.51; in males: 1.41). Conclusions: The prevalence of diabetes in the hospital is twice as high as the prevalence in the general population and has increased further with the COVID-19 pandemic, underscoring the increased morbidity in this high-risk patient group. This study provides essential information that should help to better estimate the need for diabetological expertise in inpatient care settings.
CRIS-Team Scopus Importer:2023-05-26
Keywords: COVID-19; Diabetes; DRG; hospitalization; inpatient care; trend